2010
DOI: 10.1186/2047-783x-15-12-571
|View full text |Cite
|
Sign up to set email alerts
|

Multiresistant bacteria and current therapy - the economical side of the story

Abstract: Severe infections with multiresistant bacteria (MRB) are a medical challenge and a financial burden for hospitals. The adequate antibiotic therapy is a key issue in multiresistant bacteria management. Several major cost drivers have been identified. Remarkably drug acquisition costs are not necessarily included. Most significant are the length of stay in hospital, the hours of mechanical ventilation and the time treated on an intensive care unit.In a systematic review of the literature the following aspects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 45 publications
(30 reference statements)
0
27
0
3
Order By: Relevance
“…It generates a need to develop effective and resistant antimicrobial molecules. [1][2][3][4][5][6] However, the steady discovery of novel antibiotics in the period 1940-1980 could not be sustained. Only few antibiotic classes joined the approved list after 1990 onwards.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It generates a need to develop effective and resistant antimicrobial molecules. [1][2][3][4][5][6] However, the steady discovery of novel antibiotics in the period 1940-1980 could not be sustained. Only few antibiotic classes joined the approved list after 1990 onwards.…”
Section: Resultsmentioning
confidence: 99%
“…Because of these, clinical treatment of these infections is a big clinical challenge. [2] Antibiotic-resistant bacteria are emerging as a threat to the favourable outcome of common infections in community and hospital settings. [1,2] It is either due to horizontal gene transfer or unlinked point mutations in the pathogen genome.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This drug is currently registered only for intravenous use, and a twice-daily dosing regimen is relatively easy to administer and is generally well tolerated 7 . Clinical studies have shown that tigecycline possesses an expanded spectrum of in vitro and in vivo activity against Gram-positive, Gram-negative, atypical, anaerobic, and other difficult-to-treat pathogens 8 . However, there is insufficient information on the drug's clinical efficacy for malaria treatment, as only two previous studies have demonstrated in vitro anti-P. falciparum activity for this drug 9,10 .…”
mentioning
confidence: 99%